Characterisation of titanium-rich heavy mineral concentrates from the Brahmaputra River basin, Bangladesh. (December 2014) - Rahman, M. A.; Pownceby, M. I.; Haque, N.; Bruckard, W. J.; Zaman, M. N.
<x content-type="archive" xml:space="preserve">Abstract</x> The Brahmaputra River of Bangladesh is a potential source of significant amounts of heavy mineral (HM) sand concentrates. This study provides the first ever reported characterisation data for a bulk titanium-rich HM sand sample sourced from the river system. The prepared concentrate contained ∼10–15 wt-% HMs with the remaining 85–90 wt-% of the sample comprising silicate and aluminosilicates. Modal analysis for the Fe- and Ti-rich components indicated that the HM concentrate contained 4·7% primary ilmenite, 4·4% Fe-oxide (magnetite), 0·91% titanomagnetite, 0·94% titanite and 0·08% rutile. Quantitative analysis of the ilmenite component showed the TiO2 content of the ilmenite was within the range 40–52 wt-%TiO2 (average ∼48 wt-%TiO2) with major impurities including MnO (1·83 wt-%) and MgO (0·20 wt-%) and minor impurities being Al2O3 (0·02 wt-%), Cr2O3 (0·03 wt-%), SiO2 (0·08 wt-%) and V2O5 (0·08 wt-%). Based on the composition of ilmenite and current specifications regarding ilmenite compositional purity, the most likely method for processing would be via the sulphate route.